Penyalahgunaan Wewenang Oleh Kreditur (Rentenir) Karena Tidak Dapat Membyar Hutang - Putri, Karina Marchiananda; Sarono, Agus (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2023)
This study relates to the lending and borrowing system to meet daily needs. Many people think that the credit process at banks takes a long time, so those who need money quickly will lend the money to parties who apply quickly using ID cards. Loan sharking is an act carried out by lending money in a very fast process but the interest offered is much greater than bank interest if the installments exceed the due date that must be paid. Research specifications that use analytical descriptives are intended to provide data that is as precise as possible about people, conditions or other phenomena. The approach method used is normative juridical. This study discusses: First, the implementation of the work system carried out by loan sharks in lending credit. Second, the legal consequences implemented if the customer has returned the debt but there is still interest to be paid. The results of this research show that firstly, a debtor who borrows money from a moneylender (creditor) if the deferred time has passed, then the collateral promised by both parties will inevitably be confiscated dishonorably due to the delay in payment of the debt to the moneylender. . Second, the practice of loan sharking is an illegal act that has not been regulated expressly in the laws and regulations, where this agreement arises from the practice of loan sharking which has violated the objectives contained in Article 1320 point 4, namely that it must be based on a cause that is not prohibited.